Hubungan antara Tingkat Stres dengan Beban Kerja Perawat di Rumah Sakit Semarang - Ika Chandra Putri; Dwi Heppy Rochmawati; Wigyo Susanto (NAJ Nursing Applied Journal, 2025)
Nurses are healthcare workers who have a high workload because they are in direct contact with patients 24 hours a day. Complex tasks, limited manpower, and high service demands often cause work stress. Unresolved stress can affect nurses' health, reduce performance, and even impact patient safety. This study aims to investigate the relationship between stress levels and workloads among nurses at Semarang General Hospital. The study design employs a cross-sectional approach with a quantitative methodology. The study population consists of all nurses in the inpatient ward of Semarang General Hospital, with a sample size of 80 respondents selected using proportional random sampling. The research instruments used the Perceived Stress Scale (PSS-10) questionnaire to measure stress and the NASA-TLX questionnaire to measure workload. Data analysis was conducted using the Spearman Rank test. The results of the study show that most nurses are in the moderate stress category (65%), while the highest workload is in the high category (58.8%). Bivariate analysis yielded a p-value of 0.001 (p < 0.05) with a correlation coefficient of r = 0.412, indicating a significant positive relationship between stress levels and nurses' workload. The higher the workload of nurses, the higher the stress levels they experience. Hospitals are encouraged to implement effective workload management, including proportional task distribution, additional staff, and stress management programs for nurses.